Association Of Anxiety And Insomnia With Hypertension Among Older Adults In Puskesmas Remaja - Lisa Wahidatul Oktaviani; Anisya Dea Rizkita (Sean Institute, 2024)
Hypertension is a significant health concern among the elderly, often associated with psychological factors such as anxiety and insomnia. This study aims to investigate the relationship between anxiety, insomnia, and hypertension in older adults at Remaja Health Center in Indonesia. Utilizing an analytic observational design with a cross-sectional approach, 95 elderly participants were selected using stratified proportional random sampling. Data were collected through sphygmomanometer readings, the KSPBJ-IRS insomnia questionnaire, and the ZSAS anxiety questionnaire. The results were analyzed using Spearman's rank correlation test. The findings revealed a significant and strong correlation between anxiety and hypertension, with a p-value of 0.001 and a correlation coefficient of 0.335. Similarly, insomnia also showed a significant association with hypertension, with a p-value of 0.004 and a correlation coefficient of 0.291. These results indicate that higher levels of anxiety and insomnia are linked to increased hypertension among the elderly. This study underscores the importance of addressing psychological well-being and sleep quality in managing hypertension in older adults. Routine monitoring at elderly Posyandu and interventions aimed at reducing anxiety and improving sleep could potentially mitigate the risk of hypertension in this population. Future research should explore the underlying mechanisms linking these psychological factors with hypertension and evaluate the effectiveness of targeted interventions.